Foreign bodies in esophagus - Gupta, Anchal; Gupta, Apurab; Jamwal, Padam Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The presence of a foreign body in the esophagus is a challenging problem. Perforations may result in death. Impaction mandates immediate extraction. Methods: A retrospective chart review was made of all patients hospitalized in Department of ENT, SMGS Hospital with a diagnosis of foreign bodies in the gastrointestinal tract between July 2017 to February 2018. Forty patients were identified. The charts were reviewed for the following: patient demographics, preoperative diagnosis, kind and location of the foreign body, timing of the procedure and the length of hospitalization. Results: The youngest patient in our study was 8 months old while the oldest was 60 years old. The male: female ratio of 2.3:1. The most common site of impaction was cricopharynx (55%) followed by thoracic esophagus (40%) and lower end of esophagus (5%). The most common foreign body was coin (50%) and all were seen in children upto 7 years of age. 25 (62.5%) patients were children of age less than 10 years. 20 children showed coin ingestion, 1 child of 8 months presented with impaction of fruit seed and 4 children with battery button ingestion. The length of retention of foreign body ranged from 2 hours to 6 days. All the patients were managed with rigid esophagoscopy under general anesthesia all within 12 hours of admission. Conclusions: Rigid endoscope as the instrument of choice for extracting foreign bodies from the esophagus as delay in extracting foreign bodies from the esophagus may lead to retention of foreign body and hence perforation.